Efectividad del Protocolo EDUPEC - Educación en la Cadena Pensamiento, Emoción, Conducta - en adolescentes escolarizados (2010)
ABSTRACT: The EDUPEC (Education in the relationship thought – emotion – behavior) program was developed aiming to provide strategies that enable adolescents to cope with life events and daily hassles and to contribute to the public policy of Healthy School. The protocol was based on the principles of cognitive therapy and more specifically centered in two techniques: education in the cognitive model and cognitive restructuring. To measure the efficacy of the Protocol EDUPEC, we implemented the questionnaire of positive and negative automatic thoughts (ATQ-RP) in a sample of adolescents of the municipality of Bello – Antioquia. The results evidenced statistically significant differences for negative, but not for positive thoughts, exhibiting a decrease in non-functional or negative thoughts for the experimental group.